Investigation of metrological parameters of sensors based on the pH-sensitive field effect transistors - Kukla, A. L.; Lozovoy, S. V.; Pavluchenko, A. S.; Nagibin, S. N. (Technology and design in electronic equipment, 2013)
Primary semiconductor electrodes based on the dual channel pH-sensitive field effect transistors were investigated to characterize their performance both to determine pH value of test solution and to measure sensor responses in differential mode. The simplified three-lead sensor design has been implemented for these purposes. It is shown that such parameters as accuracy, repeatability and stability of developed sensors satisfy necessary requirements for typical laboratory applications.